Exploring the Potential of Betung Bamboo Charcoal (Dendrocalamus Asper) as a Mask for Acne-Prone Facial Skin Care - Wiranda, Tessya; Rosalina, Linda (Oshada, 2024)
Acne is a common dermatological condition that negatively impacts facial appearance and self-confidence, often hindering daily activities. Bamboo charcoal derived from Dendrocalamus asper (Betung bamboo) is known to contain activated carbon, which has the ability to adsorb impurities and cleanse clogged pores, potentially reducing blackheads and acne. This study aimed to evaluate the potential of Betung bamboo charcoal as a facial mask through laboratory tests (pH, antioxidant, and antimicrobial activity), organoleptic assessments (texture, aroma, and adhesion), and hedonic tests (user preferences). A quantitative experimental approach was employed in this research. The findings revealed that the mask preparation had a pH value of 8.4, an antioxidant activity of 0.491%, and no antimicrobial activity against Staphylococcus aureus. Organoleptic evaluation showed that 71% of panelists rated the mask texture as very smooth, 86% identified the aroma as a distinctive bamboo charcoal scent, and 57% considered the mask's adhesive properties acceptable. In the hedonic test, 57% of panelists expressed overall satisfaction with the mask formulation. These results highlight the potential of Betung bamboo charcoal masks as a natural alternative for skin care, particularly for individuals with acne-prone skin. However, further improvements in antimicrobial efficacy are recommended to enhance its functional benefits.